The comparsion between traditional and new domestic architecture in Kerman, Iran - Hekmat, Afsaneh (2008)
Traditional architecture introduces the best ways of using environmental energies and adapting with nature. On the other hand new architecture is considered financial goals, follow new techniques and materials and the most using of high-priced lands. This article studies on characteristics of traditional domestic architecture and compares it with its new residential architecture in Kerman, a city of Iran. Accordingly the comparison is based on some main subjects such as house plans, construction Techniques, materials used, identities and styles of architecture. The article has also referred to the relationship between architecture and culture and climate in both traditional and new houses. Then the problem of two fabric architecture has been mentioned. Finally it has some suggestion about design of future residential buildings.